Lokasi Gedung Perpustakaan Dalam Meningkatkan Jumlah Kunjungan Perpustakaan Umum Kabupaten Gianyar Tahun 2016 - Kamajaya, Yan Robeth; Ginting, Richard Togaranta Ginting; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT The objective of this research is to know the library location in increasing the number of visits at public library in Gianyar regency in the year 2016. This research is descriptive quantitative research. The variables of this research are the library location and the number of the library user visits. The collecting of data were conducted by distributing 346 questionnaires, observation and literature study. This research is used a sampling purposive that is sampling technique with a certain considerations. Based on the result of data questionnaires processing obtained that the location of public library in Gianyar regency had significant effect on the number of the library user visits. The result of data processing showed that 346 (100%) respondents know the location of public library in Gianyar regency, 126 (36,4%) respondents live within a radius of 6 km – 15 km from the residence to the location of public library on Gianyar regency. In addition, it was found that the library location related to the aspects of access (224 respondents = 64,7%), the availability of collection (240 respondents = 69,4%), the comfort aspects (235 respondents = 68%), aspects of library facilities (227 respondents = 65,6%) and the of librarian hospitality aspects (244 respondents = 70,5%). Keywords :library location, library visit, public library.